Finite Element Evaluation of Mode I Stress Intensity Factor of Composite Material Under Domain Loading - Nasser, Ameen A.; Jasim, Haider Hadi (Basrah Journal for Engineering Sciences, 2009)
In this paper, a finite element method program under domain loading and plain strain conditions is developed and applied in evaluation of the stress intensity factor in opening mode (K1) in two dimensions crack problems. Two types of crack problems analyzed and verified: first, cracked rotating disc made from bi-directional fiber reinforced material composite, second crack blade made from bi-directional fiber reinforced metal matrix composite. It is found that the finite element method under domain loading is a good tool for the analysis of composite material. The simulation is accurate in comparison with that obtained from extrapolation method. The stress intensity factor for fiber reinforced metal matrix composite is larger when obtained from fiber-reinforced material under same condition.